122 Exercise stress echocardiography in paediatric and adolescent patients: what is the role?. (8th December 2021) - Avesani, Martina; Calvo, Giacomo; Sabatino, Jolanda; Sirico, Domenico; Castaldi, Biagio; Reffo, Elena; Cerutti, Alessia; Biffanti, Roberta; Borrelli, Nunzia; Piccinelli, Enrico; Fraisse, Alain; Padalino, Massimo; et al.
Abstract: Aims: To describe the current application of exercise stress echocardiography (ESE) in our Paediatric Cardiology Departments. Methods and results: Baseline and under stress symptoms, vital parameters, ECG, and echocardiograms from patients who underwent ESE in our centres, were retrospectively analysed and compared, as well as clinical management plans formulated based on ESEs results. Forty-five patients from Centre 1 (median age 16 years), including 87% of patients with congenital heart diseases (CHDs), and 20 patients from Centre 2 (median age 11 years), mainly tested to rule out myocardial ischemia, were included. Among patients from Centre 1, 28 had previously been treated surgically, 6 percutaneously, and 11 were under follow-up. Indications for ESE/patients' native diagnosis are illustrated in the picture. Centre 1: Exercise was maximal in 17 patients, with 2 of them having symptoms at the peak of exercise. It was stopped beforehand in 28 patients because of dyspnoea (3) and muscle fatigue (25). No arrhythmia was detected. ESE was considered as positive in 14 patients; after that, 3 patients underwent percutaneous interventions, 2 underwent cardiac surgery, 3 received indication for cardiac catheterization, 4 for advanced cardiac imaging, and 2 for exercise restriction and medical therapy. Centre 2: 15 patients (75%) completed the exercise, and none of them developed symptoms. In the remaining 25%, exercise was stopped because of muscle exhaustion. No arrhythmia was detected, and all the ESEs were negative. Comparing the cohorts, no differences in terms of ejection fraction were noticed at rest and under stress. Patients in cohort 1 were older ( P = 0.002), they achieved lower average maximal heart rate ( P = 0.0001), performed less lasting exercise ( P = 0.05), and ESE was maximal less frequently ( P = 0.005). Lastly, they had significant changes in clinical decisions ( P = 0.004). Conclusions: In paediatric cardiology, particularly in children with CHDs, ESE is a promising technique and could influence significantly clinical management plans.